Application of natural dyes in the woven pandan leaf: experimental study on craft products in Tipang village - Kamal, Fauzy Prasetya; Murwanti, Aprina; Hazmi, Fariz Al (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
Natural dyes come from natural sources through certain processes used in several arts and crafts to produce environmentally friendly products. This research aims to conduct experiments on applying natural dyes to woven pandan products in Tipang Village, North Sumatra Province. This aim was to develop sustainable methods for woven pandan leaf products. The research method uses an experimental process with a practice-led research approach to applying natural dyes in the context of arts and crafts. Experimental samples were obtained by staining using a type of mordant group, namely tegeran and tingi wood extraction, as well as a container group from fermented tarum leaves (Indigofera). The number of samples used was 6, with 1 sample without color, two with tegeran wood dye, two with tingi wood, and 1 with arum leaves. The analysis and evaluation process uses visual analysis assisted by greyscale image assessment via the Matlab application. The findings show that the application of natural dyes of the mordant group with fixation using lime has a more intense and even color quality with an R.G.B value of around 0.5 - 0.6 or an index value of around 135 -143. Meanwhile, natural dyes in the vessel class have uneven colors, so further experiments must be conducted to produce good colors. Thus, natural dyes from the mordant group can be applied to woven products made from pandan leaves.